2020
DOI: 10.1590/1678-9199-jvatitd-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Bufotenine, a tryptophan-derived alkaloid, suppresses the symptoms and increases the survival rate of rabies-infected mice: the development of a pharmacological approach for rabies treatment

Abstract: Background: Between 40,000-70,000 people die yearly of rabies, an incurable disease. Besides post-bite vaccination, no treatment is available for it. Methods: First, virus dilution for antiviral effects in mice was determined. Then, animals were treated as follows: control (NaCl 250 µL/animal/day); bufotenine (0.63, 1.05 and 2.1 mg in 250 µL of NaCl/animal/day); rabies (10-6,82 CVS dilution); and test (10-6,82 CVS dilution and bufotenine, in the above-mentioned doses). Animals were observed daily for 21 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A more sterically encumbered phenyl group at the β-position of the β-ketoesters, and bulky amine substrate also reacted without incident (entries 8, 16). Since the aromatic amines have weaker nucleophilic activity, a long reaction time was also required (entries 3,7,8,[12][13][14][15]. Moreover, electron-withdrawing groups on the benzene ring were not beneficial to the reaction (entry 15); for example, nitro groups, resulted in longer reaction times and lower conversion rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more sterically encumbered phenyl group at the β-position of the β-ketoesters, and bulky amine substrate also reacted without incident (entries 8, 16). Since the aromatic amines have weaker nucleophilic activity, a long reaction time was also required (entries 3,7,8,[12][13][14][15]. Moreover, electron-withdrawing groups on the benzene ring were not beneficial to the reaction (entry 15); for example, nitro groups, resulted in longer reaction times and lower conversion rates.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-hydroxyindole scaffold, ubiquitously present in natural products and pharmaceuticals, with demonstrated diverse biological activities [1,2], such as the selective secretory phospholipase A2 inhibitor LY31172 [3], the antibiotic agent violacein [4], the anti-influenza virus drug arbidol [5], the neurotransmitter serotonin [6], the anti-virus agent bufotenine [7], and the anti-inflammatory drug indomethacin [8] (Figure 1). To date, various protocols have been developed for its preparation [9][10][11][12][13], among which the Nenitzescu indole synthesis where 1,4-benzoquinone is condensed with enamines to afford N-substituted 5-hydroxyindoles has been proven to be the simplest strategy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these receptors may be nicotinic acetylcholine receptor (nAChR), neuronal cell adhesion molecule (NCAM) and p75 neurotrophin receptor (p75NTR) [ 21 ]. On the other hand, Vigerelli et al (2020) [ 13 ] demonstrated that nAChR does not seem to interact with alkaloids. New investigations are necessary to clarify the relationship between alkaloids and cells.…”
Section: Discussionmentioning
confidence: 99%
“…The toads of Bufonidae family have been widely studied due to the bioactive properties found in the Rhinella marina venom, which have already shown antitumor [ 13 , 14 , 15 ], antiviral [ 16 , 17 ], and antiparasitic activities [ 18 ]. The cholesterol-derived steroid structures called bufadienolides are major active compounds in the venom of Bufonidae family and are considered a promising source of bioproducts [ 19 , 20 ]. Furthermore, the alkaloids dehydrobufotenin and bufotenine also identified in R. marina venom have demonstrated to possess antiproliferative and antiviral activity, respectively [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cholesterol-derived steroid structures called bufadienolides are major active compounds in the venom of Bufonidae family and are considered a promising source of bioproducts [ 19 , 20 ]. Furthermore, the alkaloids dehydrobufotenin and bufotenine also identified in R. marina venom have demonstrated to possess antiproliferative and antiviral activity, respectively [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%